Model Pemberdayaan Pengelolaan Wisata Telaga Madirda untuk Meningkatkan Jumlah Pengunjung di Masa Pandemi COVID-19 - Yitno Puguh Martomo; Samsi Samsi; Erwinda Sam Anafih; Liem Gai Sin (Society, 2022)
Telaga Madirda, a village tourism destination managed by the Berjo Village-Owned Enterprise in Ngargoyoso Sub-District, Karanganyar Regency, Central Java, boasts an exotic natural charm ripe for development. This study investigates the empowerment model of Berjo Village-Owned Enterprise and explores innovative approaches to managing this potential tourism hotspot. Employing a qualitative descriptive method, the study utilizes an empowerment model approach across three stages: awareness, capacity building, and empowerment. Findings reveal that village leaders’ commitment bolsters Berjo Village-Owned Enterprise’s empowering process, enabling innovative event models to attract more visitors. The introduction of spiritual tourism and night camping has notably drawn individuals to Telaga Madirda, offering a retreat for relaxation and therapeutic purposes during the COVID-19 pandemic.